2015
DOI: 10.3855/jidc.5420
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance surveillance of Salmonella isolates from the First People’s Hospital of Yunnan Province, China

Abstract: Introduction: Typhoid fever is a common disease in Yunnan province; however, the resistant phenotype and epidemic characteristics of Salmonella in this area are still unclear. In this study, a 15-year surveillance of antimicrobial susceptibility of Salmonella is reported. Methodology: From January 1999 to December 2013, Salmonella isolates were recovered from patients in the First People's Hospital of Yunnan Province. Antimicrobial susceptibility was detected and data were analyzed using WHONET5.6. Results: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Even though, in this study, there were no data on the patients' history of vaccination, the data of this study showed that salmonellosis affected mostly young and middle-aged population as 92.9% of these populations have more contact with water and food that were contaminated with Salmonella [13]. The increased public standard of living resulted the reduction in the frequency of Salmonella isolation in a study in China, due to the reduced consumption of contaminated water and food [14]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though, in this study, there were no data on the patients' history of vaccination, the data of this study showed that salmonellosis affected mostly young and middle-aged population as 92.9% of these populations have more contact with water and food that were contaminated with Salmonella [13]. The increased public standard of living resulted the reduction in the frequency of Salmonella isolation in a study in China, due to the reduced consumption of contaminated water and food [14]. …”
Section: Discussionmentioning
confidence: 99%
“…A study in Pakistan showed that resistance rates of of S. Typhi and Paratyphi were 88.2% for fluoroquinolone, 66.1% for ampicillin, and 66.5% for trimethoprim-sulfamethoxazole [15]. Another study in China showed that resistance rates of S. Typhi and Paratyphi were 13.5% and 5.9% for ciprofloxacin, 5.4% and 0.8% for levofloxacin, 5.4% and 1.4% for sulfamethoxazole, 10.8% and 2.0% for ampicillin, 5.4% and 0.0% for ceftriaxone, and 0.0% for meropenem and imipenem [14]. A study in Nepal showed 1.8% resistance of S. Typhi against ampicillin and 3.9% of S. Paratyphi against ciprofloxacin, while there was no resistance against trimethoprim-sulfamethoxazole [16].…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 Our previous study found that the drug-resistance rate to third-generation cephalosporins was low in the Yunnan Province. 4 Therefore, the mechanism underlying this resistance in Salmonella is still unknown. However, outbreaks or cases of infection caused by Salmonella resistance to extended-spectrum cephalosporins have been reported around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Salmonella infections are a major cause of acute gastroenteritis and septicemia (2), and there are many infective routes, such as from feed to animal, from animal to animal, or from human to animal (3). In recent years, with the abuse of antibiotics in humans and animals, more and more multidrug-resistant Salmonella strains have been emerging (47). Therefore, the development of alternatives to conventional antibiotics is imperative, and the use of bacteriophages which infect and lyse bacteria is one of the significant options for controlling bacterial infections (8).…”
Section: Genome Announcementmentioning
confidence: 99%